VIBRATION TRANSMISSIBILITY IN SYSTEMS WITH NONLINEAR DAMPERS - Kuhnert, Willian Minnemann [UNESP]; Santade, Fransber [UNESP]; Goncalves, Paulo Jose Paupitz [UNESP]; Crocker, M. J.; Pawelczyk, M.; Pedrielli, F.; Carletti, E.; Luzzi, S. (Int Inst Acoustics & Vibration, 2015)
Dampers are used in mechanical systems to isolate them from vibration, mainly to dissipate energy and to lower the amplitude of the system behavior near the resonance frequency. However, the use of linear dampers with higher values of damping ratio amplifies the transmissibility amplitude at higher frequencies, which is not desired in vibration isolation. To investigate a possible solution to this problem, some single degree of freedom (SDOF) mechanical systems with nonlinear dampers were modeled, numerically simulated and compared to each other and also compared to a SDOF linear mechanical system, over the transmissibility and shock displacement ratio (SDR) behavior. Harmonic and shock foundation excitations were the inputs and transmissibility and SDR behavior for various equivalent damping factors were the outputs for each system. The results were compared to each other to see which dampers are better for vibration isolation in high excitation frequencies and which dampers are not. It was shown that the asymmetric damper has a specific frequency range in which it had better performance in SDR index, but for higher frequencies it became worse than the linear damper. It was also shown that the performances of the quadratic nonlinear dampers were not better than the linear system.